2013
DOI: 10.1016/j.jana.2012.08.009
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention to Decrease Intravaginal Practices in HIV-Infected Women in Zambia: A Pilot Study

Abstract: Intravaginal practices (IVP) are those in which women introduce products inside the vagina for hygienic, health, or sexuality reasons. IVP are associated with bacterial vaginosis (BV) and potentially implicated in HIV transmission. This report presents the results of a pilot study of a behavioral intervention to decrease IVP in HIV-infected women in Zambia. At baseline, all of the enrolled women (n = 40) engaged in IVP and rates of BV were high. Women receiving the intervention reported a decrease of the inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…First, we should develop appropriate public health messages to caution against harmful intravaginal practices. A pilot study among HIV-infected women in Zambia suggested that a behavioral intervention, involving an individual, interactive socio-educational session about intravaginal practices, could decrease these behaviors; communication with sexual partners regarding intravaginal practices was higher for women receiving the intervention [ 24 ]. Educational messages targeted toward or possibly delivered by influential sources of information, such as parents or male partners should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…First, we should develop appropriate public health messages to caution against harmful intravaginal practices. A pilot study among HIV-infected women in Zambia suggested that a behavioral intervention, involving an individual, interactive socio-educational session about intravaginal practices, could decrease these behaviors; communication with sexual partners regarding intravaginal practices was higher for women receiving the intervention [ 24 ]. Educational messages targeted toward or possibly delivered by influential sources of information, such as parents or male partners should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Kenyan sex workers, all women who completed the study (n=22, 96%) were in the action stage and no longer engaging in any intravaginal practice, yet the authors reported no change in odds of BV (OR: 1.00; 95% CI 0.42 to 2.38) 15. In the study of HIV-positive Zambian women, the intervention reduced intravaginal practices by 22% in the intervention arm compared with only 6% in the control arm; BV was reduced by 59% in the intervention arm and 47% in the control arm 17. In the trial of young US women the intervention was successful in reducing douching (OR: 1.34; 95% CI 1.03 to 1.73), but BV was not assessed 16.…”
Section: Discussionmentioning
confidence: 98%
“…Other interventions on intravaginal practices using a theoretical framework have been conducted among adolescents in the USA,16 HIV-positive women in Zambia17 and female sex workers in Kenya 15. These interventions ranged in size from 22 women15 to 275 women 16.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations